Applicability of Acu-TENS in Patients with Chronic Obstructive Pulmonary Disease - Melinda Harini; I Nyoman Murdana (Indonesian Journal of Physical Medicine & Rehabilitation, 2015)
Asthma and Chronic Obstructive Pulmonary Disease (COPD) are the most global prevalence disease.Accupunture has been proved to be the adjuvant therapy for both airway obstructive diseases. Butinvasive technique that were used in accupunture, is not comfortable for some patients and dependsso much to operator’s skill. Acu-TENS is an electrical stimulation therapy with low frequency,in which transcutaneous electrodes are placed over acupuncture points, Dingchuan (EX-B1). It isless invasive, easy to apply and offer advantages to patient with COPD. The Acu-TENS therapymechanism in COPD were related to lung function, functional capacity, quality of life improvement.Moreover, higher blood ß-endorphin is produced and in fact, it is found to be moderately correlatedwith reduction of respiratory rate, improvement of forced expiratory volume in one second (FEV1).Therefore, Acu-TENS could be used as alternative electrodes placement in order to improve symptoms, muscle function, and functional capacity in patients with COPD. However, long-termstudy to evaluate the application of Acu-TENS is highly recommended.Keywords: Acu-TENS, COPD, ß-endorphin